FORMATION OF LEGAL POLICY IN THE FIELD OF SECURITY AND DEFENSE OF UKRAINE: CHALLENGES, PRIORITIES, AND IMPLEMENTATION MECHANISMS (Bulletin of criminological association of Ukraine, 2025)
The relevance of the topic of legal policy-making in the field of security and defense of Ukraine is due to the complexity of the security environment in which the State operates, primarily due to the armed aggression against Ukraine, intensification of hybrid threats, and the need to adapt national legislation to NATO standards and the legal system of the European Union. The article examines the theoretical and methodological foundations of legal policy as a holistic strategy of the State aimed at ensuring national security through a developed system of legal norms, institutions and administrative mechanisms. The author substantiates that legal policy in this area should comply with the principles of consistency, legitimacy, responsibility and legal certainty, and should be capable of adaptation in the face of dynamic changes in internal and external threats. The author highlights the key challenges for lawmaking and law enforcement activities, including regulatory fragmentation, problems of balancing security needs and human rights, and threats of excessive militarization of the legal space. Attention is focused on the strategic priorities of legal policy, among which the most important are strengthening parliamentary control, effective functioning of civilian oversight institutions, creation of a single regulatory platform for the security sector, and digital transformation of management decisions. The mechanisms for implementing this policy at the level of legislative, institutional and managerial support are revealed, taking into account the practical aspects of the functioning of the security sector under martial law. The author emphasizes the need to develop a long-term model of legal policy aimed at protecting democratic values, ensuring the constitutional order and guaranteeing the stability of public administration in the field of security and defense.
Keywords: legal policy; state security; defense sector; strategic planning; legislative initiatives; civilian control; parliamentary oversight; martial law